Energy-resolved attosecond interferometric photoemission from Ag(111) and Au(111) surfaces - Ambrosio, M. J.; Thumm, U. (My University, 2018)
Photoelectron emission from solid surfaces induced by attosecond pulse trains into the electric field of delayed phase-coherent infrared (IR) pulses allows the surface-specific observation of energy-resolved electronic phase accumulations and photoemission delays. We quantum-mechanically modeled interferometric photoemission spectra from the (111) surfaces of Au and Ag, including background contributions from secondary electrons and direct emission by the IR pulse, and adjusted parameters of our model to energy-resolved photoelectron spectra recently measured at a synchrotron light source by Roth et al. [J. Electron Spectrosc. 224, 84 (2018)]. Our calculated spectra and photoelectron phase shifts are in fair agreement with the experimental data of Locher et al. [Optica 2, 405 (2015)]. Our model's not reproducing the measured energy-dependent oscillations of the Ag(111) photoemission phases may be interpreted as evidence for subtle band-structure effects on the final-state photoelectron-surface interaction not accounted for in our simulation.